PEMBERDAYAAN ZAKAT UNTUK PENGENTASAN KEMISKINAN - Aflah Binti Munawaroh (J-ESA (Jurnal Ekonomi Syariah), 2020)
Indonesia is a developing country with a large population, where the problem of poverty is still a problem for this nation which is still difficult to overcome. So it requires correct and precise handling. Poverty in Indonesia must be eradicated because it will have a major influence that can make Indonesians less prosperous. Poverty makes it difficult for someone to fulfill their daily needs. One of the efforts to alleviate this poverty problem is through the empowerment of zakat. Through the empowerment of zakat, funds of Muslims who are financially able are collected and distributed to poor Muslims. This will also train people to care for their fellow humans socially